Comparative transcriptomic analysis reveals distinct responses of beneficial bacterial endophytes to wild and cultivated rice root exudates - Francesca Vaccaro; Maria Laura Amenta; Iacopo Passeri; Camilla Fagorzi; Stefano Varriale; Danuše Tarkowská; Aleš Pěnčík; Ivan Petřík; Federica Brunoni; Vittoria Brambilla; Andrea Rossoni; Erica Mica; et al. (Plant Cell Reports, 2026)
Key message Root exudates from Oryza rufi pogon elicit stronger transcriptional responses in benefi cial bacterial endophytes and, together with bacterial inoculation, reveal distinct plant responses compared with cultivated rice, suggesting that microbiome-associated traits altered during domestication could be exploited for sustainable rice breeding. Abstract Beneficial interactions between plants and microorganisms strongly influence plant health and productivity, and root exudates play a central role in shaping these associations. In this study, we analyzed the transcriptional responses of the bacterial endophytes Enterobacter asburiae RCA24 and Kosakonia sacchari RCA25 to root exudates from two commercial Italian rice accessions ( Oryza sativa Baldo and Vialone Nano) and from an accession of the wild progenitor of tropical rice, Oryza rufipogon . Transcriptome analysis showed that RCA24 displayed distinct responses to the two O. sativa varieties, whereas RCA25 exhibited more extensive transcriptional changes in response to O. rufipogon root exudates. Differentially expressed genes were mainly associated with central metabolism, stress response, and signal transduction, suggesting distinct patterns of bacterial adaptation to the different exudate profiles. Transcriptome analysis of inoculated rice further indicated broader transcriptional changes in plants colonized by RCA24 than in those colonized by RCA25. Differentially expressed genes, particularly in shoots, were associated with defense responses, hormone-mediated signaling pathways, and ribosome biogenesis, consistent with genotype-dependent plant responses to different bacterial strains. Overall, these findings indicate that wild and cultivated rice accessions differ in their interaction with beneficial bacterial endophytes at the transcriptional level. Traits associated with plant–microbiota interactions in O. rufipogon , which are lost during domestication and diversification, may represent valuable targets for future studies aimed at enhancing beneficial microbial associations in cultivated rice.

Antagonistic interactions among Antarctic bacteria: phylogenetic and niche-based insights into bacterial communities dynamics - Giulia Semenzato; Fabiola Berti; Josselyn Stefania Cusme Valle; Elena Perrin; Angela Bechini; Carmela Calonico; Valentina Catania; Antonio Palumbo Piccionello; Anna Maria Puglia; Renato Fani (Polar Biology, 2025)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Genome-scale phylogenetic and DNA composition analyses of Antarctic Pseudoalteromonas bacteria reveal inconsistencies in current taxonomic affiliation - Emanuele Bosi; Marco Fondi; Isabel Maida; Elena Perrin; Donatella de Pascale; Maria Luisa Tutino; Ermenegilda Parrilli; Angelina Lo Giudice; Alain Filloux; Renato Fani (Hydrobiologia, 2015)

Antimicrobial activity of Pseudoalteromonas strains isolated from the Ross Sea (Antarctica) versus Cystic Fibrosis opportunistic pathogens - Isabel Maida; Emanuele Bosi; Marco Fondi; Elena Perrin; Valerio Orlandini; Maria Cristiana Papaleo; Alessio Mengoni; Donatella de Pascale; Maria Luisa Tutino; Luigi Michaud; Angelina Lo Giudice; Renato Fani (Hydrobiologia, 2015)

Genome‐scale metabolic reconstruction and constraint‐based modelling of the Antarctic bacterium P seudoalteromonas haloplanktis TAC 125 - Marco Fondi; Isabel Maida; Elena Perrin; Alessandra Mellera; Stefano Mocali; Ermenegilda Parrilli; Maria Luisa Tutino; Pietro Liò; Renato Fani (Environmental Microbiology, 2015)
Summary The A ntarctic strain P seudoalteromonas haloplanktis TAC 125 is one of the model organisms of cold‐adapted bacteria and is currently exploited as a new alternative expression host for numerous biotechnological applications. Here, we investigated several metabolic features of this strain through in silico modelling and functional integration of –omics data. A genome‐scale metabolic model of P . haloplanktis TAC 125 was reconstructed, encompassing information on 721 genes, 1133 metabolites and 1322 reactions. The predictive potential of this model was validated against a set of experimentally determined growth rates and a large dataset of growth phenotypic data. Furthermore, evidence synthesis from proteomics, phenomics, physiology and metabolic modelling data revealed possible drawbacks of cold‐dependent changes in gene expression on the overall metabolic network of P . haloplanktis TAC 125. These included, for example, variations in its central metabolism, amino acid degradation and fatty acid biosynthesis. The genome‐scale metabolic model described here is the first one reconstructed so far for an A ntarctic microbial strain. It allowed a system‐level investigation of variations in cellular metabolic fluxes following a temperature downshift. It represents a valuable platform for further investigations on P . haloplanktis TAC 125 cellular functional states and for the design of more focused strategies for its possible biotechnological exploitation.

Phenotypic and genomic characterization of the Antarctic bacterium Gillisia sp. CAL575, a producer of antimicrobial compounds - Isabel Maida; Marco Fondi; Maria Cristiana Papaleo; Elena Perrin; Valerio Orlandini; Giovanni Emiliani; Donatella de Pascale; Ermenegilda Parrilli; Maria Luisa Tutino; Luigi Michaud; Angelina Lo Giudice; Riccardo Romoli; et al. (Extremophiles, 2014)